Pengembangan Video Animasi Berbasis Inquiry Learning Tema Lingkunganku Untuk Melatih Kemampuan Berpikir Kreatif Siswa Kelas VII - Khofifah, Ida; Nulhakim, Lukman; Resti, Vica Dian Aprelia (PendIPA Journal of Science Education, 2025)
The uniformity of student responses, which tends to indicate convergent thinking or mere knowledge reproduction, warrants attention as it reveals the students' cognitive process.Therefore, learning media that can stimulate students' creative thinking processes more optimally are needed. This study aimed to obtain data and describe the efficiency level of inquiry learning-based animated videos with the theme "My Environment" to train creative thinking skills of 7th-grade students. The method used is Research and Development (R&D) with the Borg and Gall model, modified into 7 steps: problem analysis, data collection, product design, product validation, product revision, product trial, and revision of trial results. The research subjects are material experts, media experts, practitioners, and students. The data types used are expert validation sheets to test validity by material experts, media experts, and practitioners, as well as student response questionnaires to determine the product's efficiency level. The results show that based on material expert validation, the percentage is 88.6% with the category "Very Valid", media expert validation obtains a percentage of 92.4% with the category "Very Valid", and practitioner validation (science teachers) obtains a percentage of 90.3% with the category "Very Valid". The efficiency level of the animated video product obtains a percentage of 86.9% with the category "Very Efficient".